Pendidikan Kesehatan dan Sosialisasi GEMOI (Gemar Makan Ikan) pada Anak Anak SD Negeri Pantai Sumpang Binagae Kab. Barru - Kubangun, Nur Aida; Pannyiwi, Rahmat; Ningsih, Warti; Reffita, Lea Ingne; Mainassy, Meillisa Carlen; Afrika, Eka (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The low level of fish consumption and purchasing power in society can be caused by a lack of knowledge and insight regarding the benefits of consuming fish. Apart from that, there is still limited knowledge regarding the diversification of processed fish products because the majority of people's diet consists of animal protein from chicken and beef. Therefore, Health Education and Socialization of GEMOI (Love to Eat Fish) is needed. This socialization aims to increase elementary school age children's knowledge regarding fish and its preparations so that they can increase interest in consuming fish and help improve children's nutrition through fish consumption. exploring basic knowledge, the presenter explained the definition of fish, the benefits and nutritional content found in fish, types of fish and processed fish products with the help of presentation material in the form of posters. After participating in this socialization, the children began to look enthusiastic about consuming fish and began to know several types of fish and their preparations. After the GEMOI (fond of eating fish) socialization, there was an increase in the knowledge of the children at Barru Sumpang Binangae Public Elementary School and ultimately they were more motivated to consume more fish.